Facial expression recognition and emotional regulation in narcolepsy with cataplexy. (10th December 2012) - Bayard, Sophie; Croisier Langenier, Muriel; Dauvilliers, Yves
Summary: Cataplexy is pathognomonic of narcolepsy with cataplexy, and defined by a transient loss of muscle tone triggered by strong emotions. Recent researches suggest abnormal amygdala function in narcolepsy with cataplexy. Emotion treatment and emotional regulation strategies are complex functions involving cortical and limbic structures, like the amygdala. As the amygdala has been shown to play a role in facial emotion recognition, we tested the hypothesis that patients with narcolepsy with cataplexy would have impaired recognition of facial emotional expressions compared with patients affected with central hypersomnia without cataplexy and healthy controls. We also aimed to determine whether cataplexy modulates emotional regulation strategies. Emotional intensity, arousal and valence ratings on Ekman faces displaying happiness, surprise, fear, anger, disgust, sadness and neutral expressions of 21 drug‐free patients with narcolepsy with cataplexy were compared with 23 drug‐free sex‐, age‐ and intellectual level‐matched adult patients with hypersomnia without cataplexy and 21 healthy controls. All participants underwent polysomnography recording and multiple sleep latency tests, and completed depression, anxiety and emotional regulation questionnaires. Performance of patients with narcolepsy with cataplexy did not differ from patients with hypersomnia without cataplexy or healthy controls on both intensity rating of each emotion on its prototypical label and mean ratings for valence and arousal. Moreover, patients with narcolepsy with cataplexy did not use different emotional regulation strategies. The level of depressive and anxious symptoms in narcolepsy with cataplexy did not differ from the other groups. Our results demonstrate that narcolepsy with cataplexy accurately perceives and discriminates facial emotions, and regulates emotions normally. The absence of alteration of perceived affective valence remains a major clinical interest in narcolepsy with cataplexy, and it supports the argument for optimal behaviour and social functioning in narcolepsy with cataplexy.